The Effect of Magnetization on the Production Process of Soft Magnetic Composite Stators of Axial Flux Motors - Emir Poskovic; Fausto Franchini; Elisa Fracchia; Silvio Vaschetto; Luca Ferraris; Alberto Tenconi (IEEE Access)
Axial flux offer a promising and reliable solution for various applications. The use of soft magnetic composite (SMC) materials allows to resolve some of the challenges associated with these motors. Two axial flux motors with identical designs are devolved, with the only variation being in the preparation of the SMC stators. The effect of magnetization during the stator manufacturing process has been assessed. Various tests are conducted in order to compare the performance of the magnetized and non-magnetized stators. Distinct differences have been noted, showing some advantages for the prototype with aligned SMC material. These results are further explained through microstructural analyses.